«Эпохa возрождения » в Ирaне и его проявление в персидской литерaтуре (Вестник КазНУ. Серия Востоковедения, 2017)
In this article the review of political and social problems in Iran at thebeginning of the twentieth century and its manifestation in the Persian literatureis revealed. And also it is told about subjects which were touchedduring this period in the Persian literature.